Centrifuge assessment of the effects of polymer treatment on penetrometer response. Issue 5 (20th September 2017) - Reid, David; Fourie, Andy
Abstract : A series of cone and T-bar penetration tests were undertaken in a beam centrifuge on two samples of the same material prepared and consolidated from a low plasticity slurry, where one sample had undergone polymer treatment with a high molecular weight polymer and the other was untreated (UT). The material had previously been characterised through a series of comparison laboratory tests, under UT and polymer-treated (PT) conditions. The results of the centrifuge testing indicated significant differences with respect to penetrometer response, with the PT material dilating and UT contracting at high penetration rates. Further, the penetrometer results provided significantly different inferences of the material type and behaviour between the two samples – inferred differences that were in some cases contradictory to laboratory results. The implications of these results for in situ investigations of PT tailings deposits are outlined.